A Stable and Efficient Hematite Photoanode in a Neutral Electrolyte for Solar Water Splitting: Towards Stability Engineering. Issue 13 (22nd May 2014) - Kim, Jae Young; Jang, Ji‐Wook; Youn, Duck Hyun; Magesh, Ganesan; Lee, Jae Sung
<x xml:space="preserve">Abstract</x> A stable and efficient hematite photoanode that works for solar water splitting, even in a neutral electrolyte, is developed by surface modification with phosphate ions. By preventing performance and stability degradation in a neutral electrolyte, the current method provides an effective path to the stability engineering of photoelectrodes to employ any electrolyte of choice. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>